Continuing Professional Development status in the World Health Organisation, Afro-region member states - Olivia B. Baloyi; Mary Ann Jarvis (Elsevier, 2020)
There is evidence of underperformance of the Global Health Indicators, particularly in the WHO Afro-region. Yet, quality, effective healthcare delivery, and access to information about best practice remains a challenge to nurses and midwives in the WHO Afro-region. For nurses and midwives to have the capacity to practice safely and competently they need to engage in mandatory Continuing Professional Development (CPD). However a composite picture is not available for future project planners, researchers, and policy developers. Published literature from the past five years and professional body webpages were searched. The results of shining a light on the WHO Afro-region member states' CPD status revealed strengths, weaknesses, opportunities, and threats. The strengths lay in the beginnings of mandatory CPD and annual licensure renewal, while the weaknesses revealed inequity of CPD distribution across the region. The opportunities showed international academic partnership with possibilities for further engagement, and the threats were evident in the health context of the Afro-region, the shortage of nurses and the lesser participation of nurses in CPD programs. The illumination of the CPD status in the Afro-region suggests that a revised CPD landscape is necessary to strengthen the relevance and response capacity of nurses and midwives, as key contributors towards the Global Health Indicators.